Fundamentals of Materials Science, Materials for Nuclear Power Generation
Este conjunto de animaciones brinda una mejor comprensin̤ de los materiales empleados en la generacin̤ de energa̕ nc͠lear. Abarca los siguientes elementos:Nuclear reactor simulationGraph of macroscopic cross sectionDisplacement spikesDescription of dislocation loopsAtomic mass and choice of moderator